HIV-1 Transactivator of Transcription (Tat) Co-operates With AP-1 Factors to Enhance c-MYC Transcription - Alves de Souza Rios, Leonardo; Mapekula, Lungile; Mdletshe, Nontlantla; Chetty, Dharshnee; Mowla, Shaheen (Frontiers in Cell and Developmental Biology, 2021)
HIV-1 infection often leads to the development of co-morbidities including cancer. Burkitt lymphoma (BL) is one of the most over-represented non-Hodgkin lymphoma among HIV-infected individuals, and displays a highly aggressive phenotype in this population group, with comparatively poorer outcomes, despite these patients being on anti-retrovoral therapy. Accumulating evidence indicates that the molecular pathogenesis of HIV-associated malignancies is unique, with components of the virus playing an active role in driving oncogenesis, and in order to improve patient prognosis and treatment, a better understanding of disease pathobiology and progression is needed. In this study, we found HIV-1 Tat to be localized within the tumour cells of BL patients, and enhanced expression of oncogenic c-MYC in these cells. Using luciferase reporter assays we show that HIV-1 Tat enhances the c-MYC gene promoter activity, and that this is partially mediated via two AP-1 binding elements located at positions -1128 bp and -1375 bp, as revealed by mutagenesis experiments. We further demonstrate, using pull-down assays, that Tat can exist within a protein complex with the AP-1 factor JunB, and that this complex can bind these AP-1 sites within the c-MYC promoter, as shown by invivo chromatin immunoprecipitation assays. These findings therefore show that, in HIV-infected individuals, Tat infiltrates B-cells, where it can enhance the expression of oncogenic factors, which contributes towards the more aggressive disease phenotype observed in these patients.